Drugs targeting the retinoblastoma binding protein 6 (RBBP6): "the collision of computers and biochemistry" - Twala, Charmy Starnod (My University, 2017)
Screening methodologies have identified specific targets that could serve as potential therapeutic markers in cancer drug design, and the Retinoblastoma binding protein 6 (RBBP6) which is predominately expressed in lung and breast cancers is one critical protein identified. This study seeks to understand the 3D structure of RBBP6 domains, with emphasis on cancer. Three of these domains have been studied in this project, i.e. the Domain With No Name (DWNN), RING Finger, and the p53-binding domain. The ubiquitin-like structure of the DWNN has implicated this domain as a ubiquitin-like modifier of other proteins such as p53, whilst the RING Finger domain has intrinsic E3 Ligase activity like MDM2 the prototypical negative regulator of p53. The DWNN and RING Finger domains have resolved solution NMR structures, whilst the p53-binding domain has none. Thus, the first initiative undertaken was to model the RBBP6 p53-binding domain using I-TASSER and eThread-Modeller web-severs. Our results demonstrated that this domain mainly constitutes of alpha-helices and loop structures. Structural quality validations of both I-TASSER and eThread-Modeller models were further assessed using Swiss-Model and ProSA (Protein structure analysis) web-servers. Analyses were focussed on specific statistical parameters (Anolea, DFire, QMEAN, ProCheck and the ProSA Z-score). Results from these analyses show that the first I-TASSER model is the best possible representation of the RBBP6 p53-binding domain depicting minimal deviation from native state. Furthermore, screening and docking studies were performed using Schrödinger-Maestro v10.7: Glide SP and drug-like molecules that would potentially serve as agonist or antagonist of RBBP6 were identified.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the Master of Science degree. 2 November 2017.
Keywords: Breast--Cancer; Lung--Cancer; Protein binding; Cancer--Treatment